Binding of Fibronectin to SsPepO Facilitates the Development of Streptococcus suis Meningitis. (15th December 2017) - Liu, Feng; Li, Jinquan; Yan, Kang; Li, Huan; Sun, Chengfeng; Zhang, Shuo; Yuan, Fangyan; Wang, Xiangru; Tan, Chen; Chen, Huanchun; Bei, Weicheng
Abstract : In this study, we showed that the SsPepO-fibronectin-integrin interaction is important for S suis adherence to human brain microvascular endothelial cells, which facilitates the development of S suis meningitis. Abstract: Background: SsPepO is an important virulence in Streptococcus suis . Methods: In this study, we showed that SsPepO contributes to the human fibronectin-mediated adherence ability of S. suis to human brain microvascular endothelial cells. Results: The addition of an antifibronectin antibody or an arginine-glycine-aspartic acid peptide that blocks fibronectin binding to integrins significantly reduced adherence of the wild-type but not the SspepO mutant strain, indicating the importance of the SsPepO-fibronectin-integrin interaction for S. suis cellular adherence. Conclusions: By analyzing Evans blue extravasation in vivo, we showed that the interaction between SsPepO and human fibronectin significantly increased permeability of the blood-brain barrier. Furthermore, the SspepO mutant caused lower bacterial loads in the brain than wild-type S. suis in models of meningitis. These data demonstrate that SsPepO is a fibronectin-binding protein, which plays a contributing role in the development of S. suis meningitis.